2. Упростите выражение

(а - 9)^2 - (81 + 2а).

3. Разложите на множители:

а) х^2 - 49; б) 25х^2 - 10ху + у^2.

4. Решите уравнение

(2 - х)^2 - х (х + 1,5) = 4.

5. Выполните действия:

а) (у^2 - 2а) (2а + у^2); б) (3х2 + х)^2; в) (2 + т)^2 (2
- т)^2.

6. Разложите на множители:

а) 4х^2y^2 - 9а^4; б) 25а^2 - (а + 3)^2; в) 27т^3 + п^3.
Помогите,пожалуйста))

1
(у - 4)^2=у^2-8y+16
(7х + а)^2=49x^2+14xa+a^2
(5с - 1) (5с + 1)=5c^2-1=25c^2-1
(3а + 2b) (3а - 2b)=3a^2-2b^2=9a^2-4b^2

Ответы и объяснения

2014-03-12T00:12:41+04:00
(а - 9)^2 - (81 + 2а)=а^2-18a+81-81+2a=a^2-16 a
х^2 - 49=(x-7)(x+7) 25х^2 - 10ху + у^2=5x^2-y^2
дальше справишься?
да